Revivalism of Silk Routes: CPEC and South Asia-Central Asia Connectivity - Dr. Adam Saud (Journal of Political Studies, 2018)
Silk Routes remained central to the connectivity between Turkestan (Today’s Central Asia) and Hindustan (Today’s South Asia) throughout the history. Weather it was trade or military expeditions, this region remained at the hub of all such activities. Many of the rulers and invaders to Hindustan came either from Afghanistan or Turkestan. With the disintegration of former Soviet Union and emergence of independence Central Asian states, Pakistan got an opportunity to interact with these states but due to domestic, regional and international political situation, Islamabad could not draft a sound and successful policy towards the region. With the introduction of OBOR and especially CPEC, Pakistan got a golden opportunity to gain central position in South Asia-Central Asia connectivity. This article tries to explore the areas of cooperation and conflict between South Asian and Central Asian regions and the prospects for future connectivity between the two. It would try to address questions; what is the current state of relationship between Pakistan and Central Asian states? What are the impacts of Afghan instability on south Asia-central Asia connectivity in general and Pakistan-Central Asia connectivity in particular? And what are the prospects of South Asia-Central Asia connectivity through CPEC? Interpretive, critical and explanatory approaches would be used for this research and both Realism and Complex Interdependence theories would be applied.